Penguatan ekonomi kerakyatan melalui pelatihan pembuatan label dan pemasaran produk homemade - Ainur Rofiq Hafsi; Laili Amalia; Ukhti Raudhatul Jannah; Lili Supardi (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2023)
The village of Konang produces several home-made products that are managed by residents. One of the products produced is a snack, namely krupuk puli. The product is still packaged in a simple way. The product is packaged in a thin clear plastic and tied with raffia rope and without a label. Marketing of this product is also still on a small scale and limited scope. The purpose of this activity is to increase the knowledge and skills of UMKM actors in Konang Village regarding packaging, product labeling and product marketing. The method used is 5 stages: (1) Field Survey, (2) Coordination with Village Apparatus and Community, (3) Program Socialization, (4) Program Implementation, (5) Program Evaluation. The result of this service activity is the increase in knowledge and skills of Puli chips business owners in making attractive product labels and packaging, being able to make product innovations and market products with a wider scope.